2022
DOI: 10.1177/00031348221135774
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy for Pheochromocytoma: Complications and Predictive Factors of Intraoperative Hemodynamic Instability

Abstract: Background Surgery is the treatment of choice for pheochromocytoma. However, this surgery carries a risk of hemodynamic instability (HDI). The aim of this study was to report complications associated with this procedure, to identify risk factors for HDI during surgery, and its impact on postoperative outcomes. Methods The charts of all patients who underwent adrenalectomy for pheochromocytoma in two academic centers between 2006 and 2020 were retrospectively reviewed. The primary outcome was HDI defined by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…However, we did not observe any significant 30-day complications in these cases. The average rate of perioperative complications of LA reported in the literature ranges from 0 to 18.6%, with bleeding being the most frequent complication [2,8,20,26,27,29,30]. The observed complication rate of 5.6% in our analysis is in line with the above studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we did not observe any significant 30-day complications in these cases. The average rate of perioperative complications of LA reported in the literature ranges from 0 to 18.6%, with bleeding being the most frequent complication [2,8,20,26,27,29,30]. The observed complication rate of 5.6% in our analysis is in line with the above studies.…”
Section: Discussionsupporting
confidence: 91%
“…Taking into consideration the variety of indications for LA in this heterogenous group of patients, the essential role of the multidisciplinary team, including urologists, surgeons, endocrinologists, and anaesthesiologists, in the qualification of patients for surgery should be emphasized. This refers particularly to a group of patients with pheochromocytoma, who are at high risk of intraoperative haemodynamic instability [10,20,21]. The cooperation of the multidisciplinary team minimized the cardiovascular 30-day complications (1.4%) and contributed to the survival of all operated patients (mortality rate 0%).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on HDI in PPGL have focused on predicting risk factors for its occurrence 14,[28][29][30][31][32] . This study rst found the association between HDI and long-term persistent hypertension in PPGL patients after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of their correlations remains doubtful, considering the profound evolvement of diagnostic modalities, anesthetic monitoring, as well as surgical approaches. Recent studies indicated that despite optimal α-blockade, intraoperative hemodynamic fluctuations were still common but rarely associated with major cardiovascular events 12 , 13 . Prolonged α-blockade predicted more perioperative hypotension episodes 14 .…”
Section: Introductionmentioning
confidence: 99%